The night I flunked my field trip - Winkler, Henry, 1945- (Winkler, Henry, 1945- Hank Zipzer, 2004)
Fourth-grader Hank, while on a field trip aboard "The Pilgrim Spirit," tries to learn knot tying in his own unique way, which causes unforeseen problems.